Design Of Polymeric Based Composite Automotive Bumper Fascia - Sudin, Mohd Nizam (2003)
An automobile bumper fascia is a non-structural component, which contributes to vehicle crashworthiness during front or rear collisions. In the past, the fascia was made of plastic material. The weight reduction in bumper fascia without sacrificing the safety of the car passenger was extensively studied. In this research, the bumper fascia made of polymeric based composite material is designed in solid modelling software. The polymeric based composite material was selected because it can offer low weight, high specific stiffness, high specific strength, high-energy absorption and easy to produce complex shapes. Four conceptual designs of bumper fascia were developed in 3-D solid model. To decide the final design of bumper fascia the matrix evaluation method was used. The weight of bumper fascia was obtained through weight analysis that has been developed by using Pro/Engineer software. The fascia was successfully designed with less weight compared to the current fascia.